PENENTUAN STOCK BAHAN BAKU GUNA MEMINIMALISIR BIAYA PENYIMPANAN DAN MENGURANGI KERUSAKAN PADA CV SARANA MITRA SUKSES - Putra, Dheni Rahmat; Widiasih, Wiwin (JURNAL REKAYASA SISTEM INDUSTRI, 2024)
This research is aimed at finding out the amount of security stock, estimated total cost of inventory, optimal ordering, and reorder point. This study uses quantitative methods and aims to provide proposals for inventory control using continuous review systems and forecast analysis, as well as to determine the root cause of the occurrence of damage to raw materials on CV. Sarana Mitra Sukses is located in Karangnongko, Sukodono, Sidoarjo. In order to obtain the cost of providing glass 102x137 (2 mm), we experienced savings of Rp 18.105.803 with 12 sheet safety stock and re-purchase of raw materials when the raw material remains 55 sheets. For the costs of supplying glass 122x86 (2 mm), we experienced a saving of Rp 17.796.105 with 13 sheet safety stock and re-purchase when the raw material remains 57 sheets. For the supply of glass 122×102 (2 mm), we suffered savings in the amount of Rp 14.265.057 with a safety stock of 15 sheet safety stock and re-purchase when the raw material remains 67 sheets. For the supply cost of glass 88x147 (2 mm), we experienced a reduction in the size of Rp 21.599.803 in the safety stock of 19 sheet safety stock and re-purchase when the raw material remains 87 sheets. For 244x183 (3mm) glass storage costs, there are savings of Rs. 26.150.792 with 13 sheet safety stock and re-purchase when the raw material remains 58 sheets. And for the 305x214 (5mm) glass storage cost, there is a savings amounting to Rs. 20.017.022 with 3 sheet safety stock and re-purchase when the raw material remains 13 sheets. It can be seen that the total cost of inventory using the Continuous Review System method is considered more economical and can also have safety stock reorder point.